A nonsurgical approach with repeated orthoptic evaluation is justified for most blow-out fractures. Issue 6 (June 2020) - Jansen, Jesper; Dubois, Leander; Maal, Thomas J.J.; Mourits, Maarten P.; Jellema, Hinke Marijke; Neomagus, Patricia; de Lange, Jan; Hartman, Lidy J.C.; Gooris, Peter J.J.; Becking, Alfred G.
Abstract: Objective: This study presents the results of an updated clinical protocol for orbital blow-out fractures, with a special emphasis on nonsurgical treatment and orthoptic evaluation of functional improvement. Methods: A two-centre multidisciplinary prospective cohort study was designed to monitor the results of a clinical protocol by assessing ductions, diplopia, globe position, and fracture size. Patients underwent clinical assessment and orthoptic evaluation at first presentation and then at 2 weeks and 3/6/12 months after nonsurgical or surgical treatment. Outcome parameters were field of binocular single vision (BSV), ductions, degree of enophthalmos, a diplopia quality-of-life (QoL) questionnaire, and other sequelae or surgical complications. Results: 46 of the 58 patients who completed the 3, 6 and/or 12-month follow-up received nonsurgical treatment. There was full recovery without diplopia or enophthalmos (>2 mm) in 45 of the 58 patients. The other 13 patients had limited diplopia, mainly in extreme upward gaze (average BSV 90). Five of those 13 patients did not experience impairment of diplopia in daily life. The average QoL score at the end of follow-up was 97. No patients developed late enophthalmos. Conclusion: This study showed that a high percentage of patients with orbital floor and/or medial wall fracture recovered spontaneously without lasting diplopia or cosmetically disfiguring enophthalmos. The conservative treatment protocol assessed here underlines the importance of orthoptic evaluation of functional parameters.